Understanding DB2 : learning visually with examples - Chong, Raul F. (IBM Press/Pearson, 2005)
The Easy, Visual Guide to IBM DB2 V8.2 IBM DB2 Universal Database"!V8.2 for Linux®, UNIX®, and Windows® is a flexible, scalable, cost-effective, and easy-to-use enterprise database. Now, one book makes DB2 even easier. Understanding DB2 teaches DB2 V8.2 visually, step by step, with dozens of examples and case studies drawn from the authors' unsurpassed experience as DB2 consultants at IBM. Understanding DB2 doesn't just present the big picture. It thoroughly introduces every DB2 concept, procedure, and tool you'll need to get results as an administrator, user, or developer. You'll find authoritative coverage of installation, configuration, objects, database instances, storage, connectivity, security, performance, backup and recovery, SQL fundamentals, and much more. Virtually every new concept is explained with screenshots, diagrams, or tables, all designed to help you learn faster and remember more. For those preparing for certification, this book also contains over a hundred sample questions crafted by the authors to reflect the content and format of the IBM DB2 UDB Database Administration Certification exams, with answers and detailed explanations. Coverage includes Understanding the DB2 product family, DB2 commands, and the DB2 environment Configuring client and server connectivity: walkthroughs of four typical scenarios Managing DB2 storage: partitions, tablespaces, buffer pools, and more Leveraging the power of SQL: queries, inserts, deletes, and updates Implementing security: encryption, authentication, and authorization Administering and maintaining data, from LOAD and EXPORT to backup/recovery Providing high availability with online split mirroring and suspended I/O DB2 architecture: process and memory models Managing database performance and troubleshooting